Extraterrestrial soils - certini g.; SCALENGHE, Riccardo (2011)
Extraterrestrial soils may be defined as any of the solid granular crustal features of planets and moon other than those soils on planet Earth. Despite four decades of space exploration, which greatly expanded our understanding of the Solar System, there is considerable debate as to the loose covers of rocky planets and moons are soils in a pedological sense. On Earth, soil form thanks to the combined action of at least five factors: parent rock, climate, topography, living organisms and time. A few other factors can concur to drive pedogenesis. However, the necessity of biota as unavoidable soil forming factor is debated. In fact, important parts of Earth, such as the hyperarid Atacama Desert of Chile and the Dry Valleys of Antarctica, host virtually life-free soils with advanced horizonation. Actually, although most people invokes the ability to support plant growth in its natural environment as condicio sine qua non for soil, a scientific definition considers soil to be any in situ weathered veneer of a planetary surface that retains information on its climatic and geochemical history. A current or past mineral weathering is hence the pivotal requisite for soil.